Integrasi Islam dan Sains di Lembaga Pendidikan Islam: Studi Atas Pesatnya Arus Modernisasi - Anwar, Misbakhul (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study aims to analyze the evolution of Islamic education in Indonesia, recognizing its pivotal role as a driving force for national progress and human advancement. Education, being a fundamental tool in societal development, must remain responsive to the evolving needs and dynamics of society. Employing a descriptive qualitative methodology, this research adopts a library research approach to delve into the subject matter. The findings of this study underscore the centrality of the Quran in Islamic education, serving as its foundational pillar and primary source of guidance. Islamic education, contrary to a dichotomous view of knowledge, emphasizes integration, harmonizing religious teachings with contemporary knowledge systems. The integration of Islamic religious education with modern sciences and technology is envisaged to imbue learning with depth and accessibility. Furthermore, Islamic education endeavors to instill comprehensive understanding, appreciation, and adherence to Islamic principles, fostering virtuous character and devoutness among learners. This pedagogical objective is pursued through various instructional methods, including teaching, training, and experiential guidance activities. The scholarly discourse surrounding the interface between Islamic and general sciences delineates three predominant typologies: Restorationist, Reconstructionist, and Reintegrationist. While differing in approach, these typologies converge on the notion of integration and interconnection between Islamic and general sciences, emphasizing a holistic perspective. In conclusion, this research illuminates the dynamic landscape of Islamic education in Indonesia, advocating for its alignment with contemporary needs and advancements. By fostering integration and harmonization between Islamic teachings and modern knowledge systems, Islamic education endeavors to nurture individuals equipped with profound religious insight and worldly wisdom, contributing to the holistic development of society.